Population fluctuations of two Pratylenchus SPP. in maize fields with an attempt to correlate numbers with changes in certain ecological conditions - Storey, S. G.(Sheila Grace) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1985.